Speech Function on EFL Classroom Discourse Interaction at University of Riau Kepulauan: SFL Theory - Ashari, Erwin; Shalehoddin, Shalehoddin (English Department, University of Riau Kepulauan, Batam,Indonesia, 2018)
The aims of this research are to to investigate, formulate and reason speech functions and its realization coding used on EFL classroom interaction discourse at Universitas Riau Kepulauan.by using A descriptive research design by taking nine subject materials as the source of the data. They are They are; Curriculum and Material Development, Cross Culture Understanding, Statistik Pendidikan, Morphology, TEFL, Language Testing, Syntax, English Teaching Media and Prose subject materials. The result shows that the most dominant coding was congruent coding, the reason of chosing dominant coding was influenced by two facor, they were; subject material and the formality of the situation. By using he congruent coding, the students could understand the message of the subject materials rather than metaphor coding, because metaphore coding refers to the daily interaction with complext contextual relation.